Artemisinin Represses Telomerase Subunits and Induces Apoptosis in HPV‐39 Infected Human Cervical Cancer Cells. Issue 9 (September 2015) - Mondal, Anushree; Chatterji, Urmi
ABSTRACT Artemisinin, a plant‐derived antimalarial drug with relatively low toxicity on normal cells in humans, has selective anticancer activities in various types of cancers, both in vitro and in vivo. In the present study, we have investigated the anticancer effects of artemisinin in human cervical cancer cells, with special emphasis on its role in inducing apoptosis and repressing cell proliferation by inhibiting the telomerase subunits, ERα which is essential for maintenance of the cervix, and downstream components like VEGF, which is known to activate angiogenesis. Effects of artemisinin on apoptosis of ME‐180 cells were measured by flow cytometry, DAPI, and annexin V staining. Expression of genes and proteins related to cell proliferation and apoptosis was quantified both at the transcriptional and translational levels by semi‐quantitative RT‐PCR and western blot analysis, respectively. Our findings demonstrated that artemisinin significantly downregulated the expression of ERα and its downstream component, VEGF. Antiproliferative activity was also supported by decreased telomerase activity and reduced expression of hTR and hTERT subunits. Additionally, artemisinin reduced the expression of the HPV‐39 viral E6 and E7 components. Artemisinin‐induced apoptosis was confirmed by FACS, nuclear chromatin condensation, annexin V staining. Increased expression of p53 with concomitant decrease in expression of the p53 inhibitor Mdm2 further supported that artemisinin‐induced apoptosis was p53‐dependent. The results clearly indicate that artemisinin induces antiproliferative and proapoptotic effects in HPV‐39‐infected ME‐180 cells, and warrants further trial as an effective anticancer drug. J. Cell. Biochem. 116: 1968–1981, 2015. © 2015 Wiley Periodicals, Inc.